Berg Balance Scale (BBS) for Early Detection of Fall Risk in the Elderly in the Work Area of Antang Health Center Makassar City - Siti Rahmani; Tut Handayani (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Abstract: Falling is one thing that cannot be avoided by everyone, especially the elderly who are affected by a decrease in muscle strength which is one of the factors for falling. The purpose of this study is to early detect the risk of falling in the elderly using the BBS (Berg Balance Scale) questionnaire and find out the age group of the elderly who are prone to experiencing high falling risks. The method used in this study is descriptive research with sampling techniques using purposive. The risk of falling is measured using a BBS (Berg Balance Scale) observation sheet. The results showed that respondents aged 60-74 years with a total of 77 people included in the low fall risk category, there were 64 elderly (83.1%), medium fall risk 12 elderly (15.6%) and respondents with a high risk of falling 1 elderly (1.3%). The conclusion of this study is that as you get older, especially 66 years old and above, the risk of falling will also increase, so it takes awareness of yourself and your family to pay attention to each other to be able to avoid falling.